Intracranial cortical responses during visual-tactile integration in humans. - Quinn, B; Carlson, C; Doyle, W; Cash, S; Devinsky, O; Spence, C; Halgren, E; Thesen, T (2014)
Sensory integration of touch and sight is crucial to perceiving and navigating the environment. While recent evidence from other sensory modality combinations suggests that low-level sensory areas integrate multisensory information at early processing stages, little is known about how the brain combines visual and tactile information. We investigated the dynamics of multisensory integration between vision and touch using the high spatial and temporal resolution of intracranial electrocorticography in humans. We present a novel, two-step metric for defining multisensory integration. The first step compares the sum of the unisensory responses to the bimodal response as multisensory responses. The second step eliminates the possibility that double addition of sensory responses could be misinterpreted as interactions. Using these criteria, averaged local field potentials and high-gamma-band power demonstrate a functional processing cascade whereby sensory integration occurs late, both anatomically and temporally, in the temporo-parieto-occipital junction (TPOJ) and dorsolateral prefrontal cortex. Results further suggest two neurophysiologically distinct and temporally separated integration mechanisms in TPOJ, while providing direct evidence for local suppression as a dominant mechanism for synthesizing visual and tactile input. These results tend to support earlier concepts of multisensory integration as relatively late and centered in tertiary multimodal association cortices.